Analisis Keterkaitan Antar Indeks Harga Saham Sektor Keuangan : Studi Pada Negara Indonesia dan Malaysia - Narisca Ulfa Viandiny (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study to know the interconnectedness between the financial sector stock price index of Indonesian and Malaysian countries. The study use daily data of  the financial stock price index variable and the tools used for the analysis is Causality. The results show that the financial sector stock price index of Indonesian and Malaysian countries are interconnected. This causes the financial sector stock price index of Indonesian country to change (increase or decrease in the previous period) it will affect the financial sector stock price index of Malaysian country in the next 1 period, and when the financial sector stock price index of Malaysian change (increase or dcrease in  the  previous period) then  it  will  affect  the  financial sector  stock  price  index  of Indonesian country in the next 1 period.Keywords: The financial sector stock price index, Causality.